Selling to strategic consumers: on the benefits of consumers' valuation uncertainty and abundant inventory. Issue 3 (15th June 2018) - Hermel, Dror; Mantin, Benny
Abstract We consider a profit-maximizing seller who encounters consumers over two periods. The consumers face valuation uncertainty in the first period, which is resolved in the second period. We show that when the seller is capacity constrained, then there is a threshold capacityabove which the seller prefers facing strategic, rather than myopic, consumers. Accounting for the seller's stocking decisions, we find that the seller may stockhigher levels of inventory when faced with strategic consumers than when faced with myopic consumers.